2019
DOI: 10.11622/smedj.2019088
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year narrative review on antimicrobial resistance in Singapore

Abstract: Antimicrobial resistance (AMR) results in drug-resistant infections that are harder to treat, subsequently leading to increased morbidity and mortality. In 2008, we reviewed the problem of AMR in Singapore, limiting our discussion to the human healthcare sector. Ten years later, we revisit this issue again, reviewing current efforts to contain it in order to understand the progress made as well as current and emerging challenges. Although a significant amount of work has been done to control AMR and improve an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…Our study is limited to the perspective of hospital pharmacists in Singapore, a developed country with well-established ASPs in acute hospitals [ 6 ]. Nonetheless, the findings are applicable to other developed countries with established ASPs interested to enhance the ASPs by harnessing the untapped potential of hospital pharmacists in the hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study is limited to the perspective of hospital pharmacists in Singapore, a developed country with well-established ASPs in acute hospitals [ 6 ]. Nonetheless, the findings are applicable to other developed countries with established ASPs interested to enhance the ASPs by harnessing the untapped potential of hospital pharmacists in the hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work exploring the views of inpatient nurses on their roles in antimicrobial stewardship found that nurses played important roles as gatekeepers in the assurance of appropriate administration of prescribed antibiotics [ 52 ]. Future cross-disciplinary studies should be considered for triangulation of findings from the perspectives of physicians, nurses, and pharmacists, since one of the thrusts in Singapore’s National Strategic Action Plan on AMR is the optimisation of antimicrobial use through the further optimisation of antibiotic prescribing in hospitals [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASPs have been emphasized as an important tool against AMR, and nationallevel guidelines are available. [11][12][13][14][15][16][17] It is, however, difficult to tell from the published literature what the actual level of penetration is, or the degree to which different components of AMS have been implemented. Where ASPs are advanced, they have reduced overall antibiotic use, cut costs, and in some instances, improved patient outcomes.…”
Section: Ams In Asiamentioning
confidence: 99%
“…Alvin et.al reviewed the changes in Singapore in terms of antimicrobial uses, regulation and AMR epidemiology in the past ten years, mainly focusing on hospital sector [35]. The antibiotic (only antibacterial drugs are included) usage during 2000-2015 in Singapore is shown in Figure 7.…”
Section: Singapore Perspectivementioning
confidence: 99%